Factors That Can Create Hypertension Disease in The Advantage of Village Raya Berastagi Distric Karo Regency in 2019 - Ernawati Barus (Institute of Computer Science (IOCS), 2020)
Hypertension is considered a serious health problem because it is often not recognized by us with few, if any, noticeable symptoms. As for the independent variables, namely age, excessive food, occupation, genetics and the dependent variable, namely hypertension. The purpose of this study was to determine the factors that can cause hypertension in the elderly in Raya Village, Berastagi District, Karo Regency in 2019. This type of research is quasi-experimental where a sample of 30 respondents through the simple random sampling technique. The type of data used is primary data taken directly from the Raya Village Office, Berastagi District, Karo Regency. The statistical test used was the Chi-Square statistical test p = 0.426. The results of the shi-square statistical test based on age obtained p = 0.426, that is, there is no relationship between age and hypertension. Based on excessive food, it was obtained p = 0.361, that is, there was no relationship between excessive food and hypertension. Based on the work, it was obtained p = 0.819, that is, there was no relationship between work and hypertension. This means that the p value is greater than the value ofa(0.05) and thus Ho is rejected and Ha is accepted, which means there is no relationship between age, excessive food and work with hypertension. Based on genetics, it was obtained p = 0.044, which is a relationship between genetics and hypertension. This means that the p value is smaller than the valuea(0.05) and thus Ho is accepted and Ha is rejected, which means that there is a relationship between genetics and hypertension. It is hoped that the elderly in Raya Village, Berastagi Subdistrict, Karo Regency, to maintain their health in order to avoid hypertension and carry out regular checks.